Integrated Renewable Energy Solutions for Coastal Conservation Areas: A Public-Private Partnership Model for Environmental Sustainability and Economic Development - Annisa Ilmi Faried; Dian Septiana Sari; Rahmad Sembiring; Saimara Sebayang; Nor Harlinda Binti Harun; Nisa Ulzannah (Universitas 17 Agustus 1945 Semarang, 2025)
This research investigates the integration of renewable energy systems within coastal conservation areas through public-private partnership (PPP) frameworks to achieve dual objectives of environmental sustainability and economic development. The study addresses the critical challenge of balancing energy infrastructure development with ecological preservation in sensitive coastal ecosystems, where biodiversity and community livelihoods are often at risk due to increasing industrial and urban pressures. A mixed-methods approach is employed, combining case study analysis, stakeholder interviews, and economic modeling, to generate a comprehensive perspective on the opportunities and constraints of renewable energy deployment in these regions. Case studies highlight successful international practices of PPPs that have facilitated renewable energy projects while safeguarding marine and coastal ecosystems. Stakeholder interviews with government agencies, local communities, and private sector representatives reveal the importance of transparent governance, shared responsibility, and inclusive participation in ensuring long-term project sustainability. Economic modeling further demonstrates that well-structured PPP models can reduce implementation costs by 30–40% while adhering to biodiversity conservation standards and regulatory frameworks. Findings underscore that renewable energy projects, when embedded within collaborative governance structures, not only contribute to reducing carbon emissions but also create employment opportunities, stimulate local economies, and enhance community resilience. This study contributes to the sustainable development literature by providing an actionable framework for integrating renewable energy infrastructure in environmentally sensitive areas through PPPs. The proposed framework emphasizes adaptive policy design, capacity building, and equitable benefit-sharing, offering practical insights for policymakers, practitioners, and researchers seeking to reconcile energy needs with ecological protection in coastal regions.